PROSES HABITUASI NILAI DISIPLIN PADA ANAK USIA DINI DALAM KERANGKA PEMBENTUKAN KARAKTER BANGSA - Susanto, Ahmad (Sosio Religi: Jurnal Kajian Pendidikan Umum, 2017)
Habituation process of early childhood’s discipline value will build good attitude, moral, personalities and behaviours on students. They will have good habit not only to themselves but also to others. Habituation process of discipline value is aimed to form noble characters, i.e. personal who is skillful at speaking, able to use gestures and symbols, creative, discipline, able to build good relationship with others, able to make any decisions wisely, able to choose between right and wrong things, and an integrative-minded person.